Why Are High-Achieving Students Susceptible to Inhibition? An Idiographic Analysis of Student Self-Identity in China - Aruna Wu; Xiaowen Li; Jing Wang; Dan Li (Frontiers in Psychology, 2019)
High-achieving students face greater expectations in competitive societies such as China, which can impede their performance. Based on previous observations regarding what we call the “inhibition phenomenon of high-achieving students,” wherein otherwise successful students show unexpectedly poor performances in collective activities of relatively unfamiliar forms, the present research analyzes the self-identity of such students and explores the underlying mechanisms that result in this inhibition phenomenon. An idiographic approach is employed to examine typical cases and their semiotic mediation in the self-identity regulative process. Two high-achieving students who exhibit the characteristics of the inhibition phenomenon are compared with another high-achieving student who appears not to be inhibited, using a multilevel and comprehensive analysis that integrates a number of aspects, such as the students’ emotional experience of the activities in relation to which the inhibition phenomenon occurs, their meaning-making regarding the activities, and their reflections on their daily school lives. The findings show that, for the inhibited students, a cued identity as being a “good student” is activated through the activities with the connotations of “being successful compared to the others” and “pursuing recognition” leading to a worsened performance; alternatively, the student not susceptible to inhibition displays an identity of being a “learner,” who focuses on the content of the activity and concrete suggestions from important others. These specific semiotic mediation processes indicate that, when self-identity is narrow and result oriented, it is easy for excessive future-oriented self-demands to be imposed, thereby bringing pressure to the individual at that moment. By contrast, a flexible and process-oriented identity facilitates an individual’s involvement in unfamiliar activities, enabling a richer, more open self-construction process.